Conservative treatment of patients with gonarthrosis at early stages (Review of literature) - Tankut, Volodymyr; Makolinets, Kyrill (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article describes modern methods of treatment for early stages of knee osteoarthritis on the basis of results of researches, carried out by Ukrainian and foreign authors. The necessity of rational approach to conservative therapy of early stages of osteoarthritis is shown. This therapy includes use of anti-inflammatory and chondroprotective drugs with compulsory combination of physiotherapeutic treatment and local laser influence on the involved joint and its adjacent tissues in a certain sequence in order to improve the effect of pharmaceutical drugs on metabolism in the joint cartilage.